Knowledge, health beliefs and attitudes towards dementia and dementia risk reduction among the Dutch general population: a cross-sectional study - J. Vrijsen; T. F. Matulessij; T. Joxhorst; S. E. de Rooij; N. Smidt (BMC Public Health, 2021)
Abstract Background Positive health beliefs and attitudes towards dementia and dementia risk reduction may encourage adopting a healthy behaviour. Therefore, we aimed to investigate the knowledge, health beliefs and attitudes towards dementia and dementia risk reduction among the Dutch general population and its association with the intention to change health behaviours. Methods A random sample of Dutch residents (30 to 80 years) was invited to complete an online survey. We collected data on knowledge, health beliefs and attitudes towards dementia (risk reduction) and the intention to change health behaviours. Multivariable logistic regression analyses were used to obtain effect estimates. Results Six hundred fifty-five participants completed the survey. In general, participants had insufficient knowledge about dementia and dementia risk reduction. Participants had relatively high scores on general health motivation and perceived benefits, but low scores on perceived susceptibility, perceived severity, perceived barriers, cues to action and self-efficacy. Individuals with higher scores on perceived benefits and cues to action had more often the intention to change their behaviour with regard to physical activity (OR = 1.33, 95%-CI:1.11–1.58; OR = 1.13, 95%-CI:1.03–1.24, respectively) and alcohol consumption (OR = 1.30, 95%-CI:1.00–1.69; OR = 1.17, 95%-CI:1.02–1.35, respectively). Younger excessive alcohol consumers with higher perceived severity scores had more often the intention to change their alcohol consumption behaviour (OR = 2.70, 95%-CI:1.04–6.97) compared to older excessive alcohol consumers. Opposite results were found for middle-aged excessive alcohol consumers (OR = 0.81, 95%-CI:0.67–0.99). Individuals who perceived more barriers had more often the intention to change their diet (OR = 1.10, 95%-CI:1.01–1.21), but less often the intention to change their smoking behaviour (OR = 0.78, 95%-CI:0.63–0.98). Moreover, less educated individuals with higher perceived benefits scores had less often the intention to change their diet (OR = 0.78, 95%-CI:0.60–0.99), while highly educated individuals with higher perceived benefits scores had more often the intention to change their diet (OR = 1.41, 95%-CI:1.12–1.78). Conclusions The knowledge, beliefs and attitudes towards dementia and dementia risk reduction among the Dutch general population is insufficient to support dementia risk reduction. More education about dementia and dementia risk reduction is needed to improve health beliefs and attitudes towards dementia and dementia risk reduction in order to change health behaviour.